Reading literacy intervention with fifth graders in Lima - Morales Silva, Silvia (2009)
This study examined the effects of the reading comprehension program Lectura for fifth graders of middle-class and low-class social economic backgrounds in Lima (Peru) on reading literacy and reading motivation. The intervention emphasized reading strategies and dimensions of reading motivation. ANOVA was used in order to calculate the effects of measurement point, group, social economic status and gender on reading comprehension and reading motivation. Results showed that reading literacy increased more in the intervention group than in the control group. Children from the low social economic background benefited more from the intervention than children with a middle social economic background. The program had also a significant impact on children’s reading motivation.